School type and principals' leadership styles as correlates of teachers’ job performance in selected education zones in Rivers State, Nigeria (2016)
In order to know the performance of teachers on the job, this study investigated school type and principals’ leadership style as correlates of teachers’ job performance in selected Education zones in Rivers State, Nigeria. The study adopted the descriptive survey design. The sample consisted of three hundred and ten (310) students and sixty (60) teachers who were randomly selected from four schools in each of the chosen education zones in Rivers State. Three research questions were raised and answered at 0.05 level of significance using Pearson Product Moment Correlation and Multiple Regression Analysis. Data were collected using two self-structured questionnaires. The reliability coefficients of 0.85 and 0.72 were obtained for SPTJPQ and TPSTPLSQ respectively using the test- retest method. The results revealed that all the predictor variables (school type, democratic, autocratic, transformational and laissez-faire leadership styles) have relationships with teachers’ job performance at varying strengths; strong positive and significant correlation exist between democratic and autocratic leadership styles; only transformational leadership style has significant relative prediction to teachers’ job performance; the five predictors jointly correlates positively (R- .215) with teachers’ job performance. It also showed that 3.1% (adjusted R2 = 0.031) of the total variance in teachers’ job performance is accounted for by the five predictors while the remaining 96.9% could be due to other factors like residuals not considered in the study. Since F(5,304) = 2.946, P< 0.05. Only transformational leadership style (J3= .188, t = 3.004, p<0.05) contributes significantly to the prediction model. Based on the findings, it was recommended that school principals and administrators should use transformational and democratic administrative leadership styles more often than any other style in carrying out their administrative roles in the schools. Principals should be neither too flexible nor too rigid in their actions, policies and decisions; they should only apply the autocratic leadership style when the situation requires it as the last option, but it must be used with caution; government should organise capacity building regularly for the principals, school administrators , and the like.